Ten Cases of Biopsy-Proven Acute Tubulointerstitial Nephritis: Report from a Single Center in a Rural Area from 2008 to 2021 - Kei Nagai; Tsuyoshi Tsukada; Akiko Sakata; Atsushi Ueda (Case Reports in Nephrology)
Acute tubulointerstitial nephritis (ATIN) can be caused by any number of factors, and it accounts for several percent of renal biopsy cases. In Japan, case reports exist, but there are few single-center series of ATIN cases. Case 1. A teenage male patient developed fever and cough on day X-61 and was found to have normal renal function and positive C-reactive protein (CRP) by his primary care physician. On day X-20, he presented with cough and nasal discharge in addition to low-grade fever, and his doctor noted renal dysfunction with serum creatinine of 2.12 mg/dL, negative urine occult blood, and positive urine glucose. Renal biopsy results showed diffuse interstitial nephritis with scarce glomerular involvement. There was no concurrent uveitis. Renal function normalized after 4 months of treatment with moderate-dose prednisolone. Cases 2–10. Of the 422 cases for which renal biopsies were performed at our institution from 2008 to 2021, acute tubulointerstitial nephritis was confirmed clinically and pathologically in 9 cases in addition to case 1, accounting for 2.4% of all biopsy cases. In the analysis of the 10 patients, the median age was 40 years old, eGFR at diagnosis was 19.4 (3.2–49.1) mL/min/1.73 m2, and 2 of them underwent hemodialysis, but both were weaned from dialysis, and the eGFR after treatment was 53.6 (20.8–110.0) mL/min/1.73 m2; all patients showed improvement (P<0.001). Treatment consisted of steroids in 8 patients and no steroids in 2 patients, the latter being treated by discontinuation of the suspect drugs and treatment of infection; 7 of the 10 patients were examined for ocular uveitis, and uveitis was diagnosed in 5 patients. The causes and clinical course of ATIN are diverse, but it is treated according to individual judgment in addition to standard treatment, and it generally has a good renal prognosis.